2003
DOI: 10.7326/0003-4819-139-12-200312160-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Use and the Risk for Melanoma: A Quantitative Review

Abstract: No association was seen between melanoma and sunscreen use. Failure to control for confounding factors may explain previous reports of positive associations linking melanoma to sunscreen use. In addition, it may take decades to detect a protective association between melanoma and use of the newer formulations of sunscreens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 46 publications
2
121
0
3
Order By: Relevance
“…This is consistent with the observations that people working outdoors with certain intervals run lower risk of developing malignant melanoma localized in the skin exposed to UV radiation than people who work indoors [58][59][60]. Continuous sun exposure may reduce a risk of sunburns, which are a known etiologic factors of malignant melanoma.…”
Section: Highlights In Skin Cancersupporting
confidence: 90%
“…This is consistent with the observations that people working outdoors with certain intervals run lower risk of developing malignant melanoma localized in the skin exposed to UV radiation than people who work indoors [58][59][60]. Continuous sun exposure may reduce a risk of sunburns, which are a known etiologic factors of malignant melanoma.…”
Section: Highlights In Skin Cancersupporting
confidence: 90%
“…Interpretational problems are also encountered with case-control studies examining the variation of risk with age at exposure, although the findings tend to concur with the migrant study results that indicate a heightened carcinogenic sensitivity at young ages (Whiteman et al, 2001). Epidemiological studies of melanoma and sunscreen use have not produced consistent results, and recent meta-analyses by Huncharek and Kupelnick (2002) and Dennis et al (2003) found no overall association. Studies of sunbed use have also tended to generate inconclusive findings.…”
Section: Ultraviolet Radiationmentioning
confidence: 82%
“…51 Two metaanalyses, however, demonstrated that after controlling for skin type and exposure, sunscreen users do not have a higher risk of melanoma. 52,53 No studies have demonstrated that sunscreen use prevents melanoma or BCC. Sunscreen continues to be recommended by the American Academy of Dermatology 54 and many other organizations as part of a total program of protection from the sun.…”
Section: Preventionmentioning
confidence: 99%